An introduction to metallurgy - Cottrell, Alan, 1919-2012 (Book (Institute of Materials (London, England)) ;, 1995)
This classic textbook has been reprinted to provide undergraduates with a broad overview of metallurgy from atomic theory, thermodynamics, reaction kinetics and crystal physics, to elasticity and plasticity.